Design a stable 14-to-20-GHz source - Moghavvemi, M.; Attaran, A.; Ameri Mahabadi, H. (2010)
Careful selection of key components and the use of straightforward multiplication schemes can be applied to the design of a low-noise frequency synthesizer for Ku-band signals to 20 GHz.